Application of Sanctions for Violations of Mandatory Reporting of Beneficial Owners in Limited Liability Companies - Victoria Tabita Majesty Lamada (Jurnal Hukum Prasada, 2024)
This research explores the concept and regulatory framework of Beneficial Owners in Indonesia's corporate governance, focusing on Limited Liability Companies. Beneficial Owners, distinct from registered shareholders, hold significant economic interests in corporations while their identities may not be publicly disclosed. The study traces the historical evolution of the Beneficial Owner concept from medieval proxy arrangements to modern corporate structures. It examines legal instruments such as Presidential Regulation Number 13 of 2018 and Minister of Law and Human Rights Regulation Number 15 of 2019, which mandate transparency in disclosing Beneficial Owners to prevent Money Laundering and Terrorism Financing. However, in reality, there is no specific law that regulates Beneficial Owners, so it is necessary to refer to the considerations for the formation of Presidential Regulation 13/2018 and the Regulation of the Minister of Law and Human Rights 15/2019. Despite regulatory advancements, compliance remains a challenge, with significant proportions of corporations failing to report Beneficial Owners annually. Sanctions, including administrative penalties and criminal liabilities under Indonesian laws, underscore the importance of enforcement to ensure transparency and accountability in corporate governance. The research highlights global implications, emphasizing the role of transparency in combating international financial crimes and promoting ethical business practices worldwide.